Risk Factors and Management Strategies for Dry Eye Syndrome: A Comparative Study - Ehsan Khalil Abed; Abbood, Aiad Ali (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2024)
Introduction: Dry eye syndrome (DES) is a prevalent multifactorial ocular surface disorder characterized by discomfort, visual disturbances, and tear film instability. This study aimed to investigate the risk factors associated with DES and compare the effectiveness of various management strategies. Methods: A cross-sectional comparative study was conducted at an ophthalmic consultant clinic from March 2023 to October 2023. One hundred patients diagnosed with DES were enrolled. Demographic data, including age, gender, and body mass index (BMI), were collected. Ophthalmological examinations, including slit-lamp examination, non-contact tonometry, fundus examination, tear break-up time (TBUT) measurement, and ocular surface disease index (OSDI) questionnaire assessment, were performed. The management strategies employed were categorized as medical, surgical, or a combination of both. Results: The study population predominantly consisted of females (70%) with a mean age of 49.65 years. The majority of patients (57%) fell within the overweight BMI category (25-29 kg/m2). TBUT values of 7 seconds and 8 seconds were most prevalent (35% and 37%, respectively), and the majority of patients (65%) reported an OSDI score of 2. Notably, two-thirds of patients received medical treatment, one-third underwent a combination of medical and surgical treatment, and a small proportion (5%) underwent surgery alone. Conclusion: Female gender, increased BMI, and older age were identified as significant risk factors for DES. Patients with DES symptoms exhibited shorter TBUT values and higher OSDI scores, indicating tear film instability and increased disease severity. Medical treatment was the most common management strategy, followed by a combination of medical and surgical interventions. These findings underscore the importance of early diagnosis and individualized treatment plans for effective DES management.